2018
DOI: 10.1186/s12881-017-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GRM7 polymorphisms on the development of noise-induced hearing loss in Chinese Han workers: a nested case-control study

Abstract: BackgroundNoise-induced hearing loss (NIHL) is a complex, irreversible disease caused by the interaction of genetic and environmental factors. In recent years, a great many studies have been done to explore the NIHL susceptibility genes among humans. So far, high powerful detections have been founded that genes of potassium ion channel genes (KCNQ4 and KCNE1), catalase (CAT), protocadherin 15 (PCDH15), myosin 14 (MYH14) and heart shock protein (HSP70) which have been identified in more than one population may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The onset is between 2 and 7 years of age, with rapid developmental regression, ataxia, myoclonus and epilepsy, and a prompt visual failure. Subsequent cases were reported in Turkey [ 18 , 22 ], Italy [ 28 ], Germany [ 29 ], Israel [ 30 ], Ireland [ 31 ], Pakistan [ 22 ], Japan [ 32 ], China [ 33 ], and Saudi Arabia [ 34 ], some showing a milder phenotype. A few highly atypical presentations reported thus far include a congenital NCL in an Argentinian female [ 35 ] and a seizure disorder with retinitis pigmentosa but normal cognition in Hispanic siblings [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset is between 2 and 7 years of age, with rapid developmental regression, ataxia, myoclonus and epilepsy, and a prompt visual failure. Subsequent cases were reported in Turkey [ 18 , 22 ], Italy [ 28 ], Germany [ 29 ], Israel [ 30 ], Ireland [ 31 ], Pakistan [ 22 ], Japan [ 32 ], China [ 33 ], and Saudi Arabia [ 34 ], some showing a milder phenotype. A few highly atypical presentations reported thus far include a congenital NCL in an Argentinian female [ 35 ] and a seizure disorder with retinitis pigmentosa but normal cognition in Hispanic siblings [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest study to assess GRM7 risk variants in an ARHL population sample tested four SNPs in elderly Taiwanese and found one associated in a dominant pattern (Chang et al, 2018). Two studies have analyzed GRM7 risk variants in relation to traits linked to ARHL; noise-induced HL in a Han Chinese sample (Yu et al, 2018) and tinnitus and ARHL in a Portuguese sample (Haider et al, 2017).…”
Section: And Idate G Ene S Tud Ie Smentioning
confidence: 99%
“…Studies focusing on GRM7 in several large human cohorts demonstrated its association with ARHL in European (Friedman et al, ; Van Laer et al, ) and American (Newman et al, ) populations but not in Chinese (Luo et al, ). Additionally, in Chinese Han workers, mutant allele C of rs1485175 in GRM7 may reduce susceptibility to noise‐induced hearing loss (Yu et al, ). These findings lend support to the role of glutamate in ARHL, and glutamate transmission may indeed represent a therapeutic target for future treatment of ARHL.…”
Section: Cochlear Synaptopathymentioning
confidence: 99%